Association of Hemoglobin Variability with Mortality in Dialysis Patients in Tertiary Hospital Nepal - Kandel, Gobinda; Sedhain, Kabindra; Thakur, Pitambar; Sapkota, Pradeep; Sapkota, Kalyan (Journal of National Heart and Lung Society Nepal, 2023)
Background: Rising number of End Stage Renal Disease patients is a great economic burden because of its high cost and lifelong treatment need. Target hemoglobin in dialysis patients is maintained through iron supplement, Erythropoietin stimulating agents, Blood products transfusions and treatment of other correctable causes. Large Hemoglobin fluctuation in such patients is related to decreased survival. The aim of this study was to relate hemoglobin variability with mortality in dialysis patients. Methods: This is a cross sectional observational study carried out in 104 patients undergoing dialysis for a duration of one year from March 2019 to February 2020. Area Under Curve (AUC) method was used to calculate hemoglobin variability. Hb data were collected using Hospital based software. Results: Mean age of study population was 50.15±14.1 yrs and 68.14% were male. Calculated hemoglobin variability was more in <15T (patients receiving less than fifteen blood transfusions per year) than >15T (patients receiving more than fifteen blood transfusions per year) group. Death to survival ratio was 0.73 in <15T and 0.41 in >15T. Conclusion: This study showed that lesser the hemoglobin variability, better the survival in ESRD population receiving maintenance hemodialysis.